Solid state composting process by fungal mixed culture from empty fruit bunches,pome and cake - Kabbashi, Nassereldeen Ahmed (s.n, 2013)
Wastes from oil palm industries are generated everyday and every year becoming a great concern consequently, an urgent development of bio-composting process has been researched. Bio composting is an environmentally way where its product could be utilized as plant growth enhancement. The study was concerning about simple composting process using substrate that has been selected in this experiment which are EFB, POME and CAKE whereas the co-substrate is sawdust. The strains of Phanerochaete Chrysosporium, Trichoderma Viride, Aspergillus Niger and Penicillium are used in this experiment